‘None of Them Know Me’: A Qualitative Study of the Implications of Locum Doctor Working for Patient Experience - Ferguson, Jane; Stringer, Gemma; Walshe, Kieran; Donnelly, Ailsa; Grigoroglou, Christos; Allen, Thomas; Kontopantelis, Evangelos; Ashcroft, Darren M. (Health expectations : an international journal of public participation in health care and health policy, 2024)
ABSTRACT Introduction There have been some concerns about the impact of temporary doctors, otherwise known as locums, on patient safety and the quality of care. Despite these concerns, research has paid little attention to the implications of locum working on patient experience. Methods A qualitative semi‐structured interview study was conducted with 130 participants including locums, people working with locums and patients with experience of being seen or treated by locums. Analysis was conducted using a reflexive thematic approach and abductive analysis to position themes against wider knowledge. Results Three main themes were constructed through analysis: (1) Awareness and disclosure; patients were not always aware if their doctor was a locum, and there was some debate about whether patients had a right to know, particularly if locum working presented quality and safety risks. (2) Continuity and accessibility of care; access was regarded as priority for acute conditions, but for long‐term or serious conditions, patients preferred to see a permanent doctor who knew their history, although it was acknowledged that locums could provide fresh perspectives. (3) Communication and practice; locums and patients described how consultations were approached differently when doctors worked as locums. Patients evaluated their interactions based on how safe they felt with practitioners. Conclusion Patients reported that they were unlikely to have continuity of care with any doctors delivering care, regardless of their contractual status. Locums sometimes provided new perspectives on care which could be beneficial for patient outcomes, but for patients with long‐term, complex or serious conditions continuity of care was important, and these patients may avoid or delay seeking care when locums are the only available option. Patient or Public Contribution Patients and carers were involved in our study from inception to dissemination. Our Patient and Public Involvement (PPI) forum was involved throughout project design and planning and gave us feedback and guidance on research materials and outputs (e.g., study protocol, participant information sheets, survey tools, interview schedules, emerging findings). Our PPI forum co‐produced our patient interview schedule, two members of our PPI forum led the patient focus groups and all were involved in analysis of patient interviews. Our PPI Chair was involved in the preparation of this manuscript.